Thermophysical properties and ecotoxicity of new nitrile functionalised protic ionic liquids - Khan, A.S. (Elsevier B.V., 2018)
In this present research, five nitrile functionalised imidazolium based protic ionic liquids (PILs) by varying alkyl chain length of anions were synthesized. The synthesized ILs were characterized with nuclear magnetic resonance spectroscopy (NMR) and elemental analyser (CHNS). Various thermophysical properties such as refractive index, density, viscosity and thermal stability were measured over wide temperature range. From the density experimental data, different volumetric properties were estimated using well established empirical equations. Moreover, the effect of temperature and increase of alkyl substitutions attached to anion has been evaluated for the studied properties. The toxicity of the synthesized ILs has been assessed against three human pathogenic bacteria i.e., Aeromonas hydrophila A97 (AH), Escherichia coli E149 (EC), and Staphylococcus aureus S244 (SA) in light to identify the influence of increasing alkyl substitution of the anion moiety on the overall toxicity of PILs. Â© 2017